The Association between Atherosclerotic Disease Risk Factors and Serum 25-Hydroxyvitamin D Concentration in Japanese Subjects - MIZUNO, Kei; WATANABE, Yasuyoshi; TANAKA, Kiyoshi; KUWABARA, Akiko; URA, Chihiro; OGASAWARA, Honami; YASUOKA, Akane; TSUGAWA, Naoko (Journal of Nutritional Science and Vitaminology, 2023)
Recent studies have described that vitamin D deficiency/insufficiency is associated with hypertension, insulin resistance, and dyslipidemia, which are major components of metabolic syndrome causing atherosclerosis. Therefore, we investigated the relationship between serum 25-hydroxyvitamin D [25(OH)D] concentration and atherosclerotic disease risk factors in healthy Japanese adults. In the present cross-sectional study, 1,177 subjects (348 males and 829 females) aged 20–72 y living in Japan (34.7–35.0ºN) were evaluated for vitamin D status by measuring serum 25(OH)D concentration. Atherosclerotic disease risk factors were defined as the presence of two or more of the following three risk factors: high blood pressure, dyslipidemia, and hyperglycemia. The percentages of vitamin D deficient and insufficient subjects were 33% and 46% in males and 59% and 32% in females, respectively. Subjects with atherosclerotic disease risk factors were significantly older and had higher BMI than those without it in both sexes. Male subjects with atherosclerotic disease risk factors had significantly lower physical activity and serum 25(OH)D concentration than those without it. In a logistic regression analysis adjusted for confounding factors, serum 25(OH)D concentration showed a significant inverse association with risk factors of atherosclerotic disease in males (OR=0.951, 95%CI: 0.906–0.998), but not in females. A covariance structure analysis also suggested that serum 25(OH)D level has a direct association with risk factors of atherosclerotic disease. In conclusion, we have demonstrated that low serum 25(OH)D level is a significant factor for increased atherosclerotic disease risk factors in males.